"Liberdade e direito": a tarefa da paz perpétua em Kant - Luciana Pereira Queiroz Pimenta Ferreira (2003)
Freedom and Law: Peace duty in Kants everlasting peace. this paper presents, under the perspective of the kantian philosophy, the disruption observed in Freedom and Law, the relationship between these two spheres, in addition to their determinant concepts, as shown in the kantian project concerning an everlasting peace. Freedom is observed in a cosmological, practical and juridical sense, establishing itself as a necessary idea to the general concept of Law. That is found in its internal, international and universal aspects, for instance, Public Law, Peoples Law and Cosmopolitan Law. All those aspects are found to conceive an everlasting peace condition. Peace is thought then as a duty to Law, sustained, in the last instance, as the bond between Morality and Law as Peace and Law instauration is also conceived, in its origins, as moral duties to Mankind